On a class of controls of the Poisson process - Grigelionis, B. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис. Об одном классе управлений пуассоновским процессом B. Grigelionis. Apie vieną Puasono proceso valdymų klasę